HIV-Infection, Atherosclerosis and the Inflammatory Pathway: Candidate Gene Study in a Spanish HIV-Infected Population - Ibáñez, Laura; Velli, Pablo Sebastián; Font, Roser; Jaén, Angeles; Royo, Josep; Irigoyen, Daniel; Cairó, Mireia; De la Sierra, Alejandro; Arranz, María Jesús; Gallardo, David; Dalmau, David (PloS one, 2014)
Higher prevalence of atherosclerosis and higher cardiovascular risk is observed in HIV-infected individuals. The biological mechanisms underlying these processes are unclear. Several studies have implicated genetic variants in the inflammatory genes in cardiovascular disease and in HIV natural course infection. In this study we have tested the possible association between genetic variants in several inflammatory genes and asymptomatic cardiovascular disease measured by carotid intima media thickness (cIMT) and atherosclerotic plaque presence as dependent variables in 213 HIV-infected individuals. A total of 101 genetic variants in 25 candidate genes have been genotyped. Results were analyzed using Plink and SPSS statistical packages. We have found several polymorphisms in the genes ALOX5 (rs2115819 p = 0.009), ALOX5AP (rs9578196 p = 0.007; rs4769873 p = 0.004 and rs9315051 p = 0.0004), CX3CL1 (rs4151117 p = 0.040 and rs614230 p = 0.015) and CCL5 (rs3817655 p = 0.018 and rs2107538 p = 0.018) associated with atherosclerotic plaque. cIMT mean has been associated with CRP (1130864 p = 0.0003 and rs1800947 p = 0.008), IL1RN (rs380092 p = 0.002) and ALOX5AP (rs3885907 p = 0.02) genetic variants. In this study we have found modest associations between genetic variants in several inflammatory genes and atherosclerotic plaque or cIMT. Nevertheless, our study adds evidence to the association between inflammatory pathway genetic variants and the atherosclerotic disease in HIV-infected individuals.